Toward Integrative Reading Science: The Direct and Indirect Effects Model of Reading - Kim, Young-Suk Grace (Journal of learning disabilities, 2020)
The authors propose an integrative theoretical model of reading called the direct and indirect effects model of reading (DIER) that builds on and extends several prominent theoretical models of reading. According to DIER, the following skills and knowledge are involved in reading comprehension: word reading, listening comprehension, text reading fluency, background knowledge (content knowledge and discourse knowledge), reading affect or socioemotions, higher order cognitions and regulation (e.g., inference, perspective taking, reasoning, and comprehension monitoring), vocabulary, grammatical (morphosyntactic and syntactic) knowledge, phonology, morphology, orthography, and domain–general cognitions (e.g., working memory and attentional control). Importantly, DIER also describes the nature of structural relations—component skills are hypothesized to have (a) hierarchical relations; (b) dynamic (or differential) relations as a function of text, activity (including assessment), and development; and (c) interactive relations. The authors then examined the hierarchical relations hypothesis by comparing a flat or direct relations model with hierarchical relations (or direct and indirect effects) models. Structural equation model results from 201 Korean-speaking first graders supported the hierarchical relations hypothesis and revealed multichanneled direct and indirect effects of component skills. These results are discussed in light of DIER, including instructional and assessment implications for reading development and reading difficulties.